Investigation of the role of ?-lipoic acid on fatty acids profile, some minerals (zinc, copper, iron) and antioxidant activity against aluminum-induced oxidative stress in the liver of male rats - Sahin, Zafer; Ozkaya, Ahmet; Yilmaz, Okkes; Yuce, Abdurrauf; Gunes, Mehmet (Walter de Gruyter GmbH, 2017)
We have investigated the effects of ?-lipoic acid (LA), a powerful antioxidant, on the fatty acid (FA) profiles, aluminum accumulation, antioxidant activity and some minerals such as zinc, copper and iron against aluminum chloride (AlCl3)-induced oxidative stress in rat liver. Twenty-eight male Wistar rats were divided into four groups as control, LA, AlCl3 and LA+AlCl3. For 30 days, LA was intraperitoneally administrated (50 mg/kg) and AlCl3 was given via orogastric gavage (1600 ppm) every other day. AlCl3-Treated animals exhibited higher hepatic malondialdehyde concentration and lower glutathione peroxidase and catalase activity, whereas these alterations were restored by the LA supplementation. Total saturated FA of the AlCl3-Treated group was higher than the LA supplementation groups. Moreover, total unsaturated FA level of the LA+AlCl3 group was higher than the AlCl3-Treated group. Hepatic zinc level of the AlCl3-Treated group was lower than the control group, whereas it was higher in the LA and the LA+AlCl3 groups. Hepatic copper levels did not significantly change in the experimental groups. Iron level was lower in the LA and LA+AlCl3 groups compared with the AlCl3-Treated group. Moreover, the liver Al concentration was found to be lower in the LA and LA+AlCl3 groups compared to the AlCl3 group. These results indicate that AlCl3 treatment can induce oxidative stress in the liver. LA supplementation has a beneficial effect on the AlCl3-induced alterations such as high lipid peroxidation, Al accumulation, FA profile ratios and mineral concentrations. © 2017 2017 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: aluminum; fatty acids; iron; liver; oxidative stress; zinc; ?-lipoic acid